Quality deterioration of bananas in the post-harvest supply chain- an empirical study - Indika Fernando; Jiangang Fei; Roger Stanley; Hossein Enshaei; Alieta Eyles (Modern Supply Chain Research and Applications, 2019)
Purpose – Quality deterioration in bananas along the supply chain (SC) due to cosmetic damage has been a persistent challenge in Australia. The purpose of this paper is to investigate the incidence of cosmetic defects in bananas across the post-harvest SC and determining the causes of the diminished fruit quality at the retail stores. Design/methodology/approach – The study quantified the level of cosmetic damage in 243 cartons of Cavendish bananas across three post-harvest SCs in Australia from pack houses to retail stores and identified the risk factors for cosmetic defects. Findings – The level of cosmetic damage progressively increased from pack house (1.3 per cent) to distribution centre (DC) (9.0 per cent) and retail (13.3 per cent) and was significantly influenced by package height and pallet positioning during transit. Abrasion damage in ripened bananas was influenced by the travel distance between DC and retail store. The study also revealed a range of risk factors contributing to the observed damage including weakened paperboard cartons due to high moisture absorption during the ripening process. Research limitations/implications – This study only investigated damage incidence in three post-harvest banana SCs in Australia and the damage assessments were confined to packaged bananas. Originality/value – This study assessed the quality of bananas along the entire post-harvest SC from farm gate to retail store. The study provided knowledge of the extent of the quality defects, when and where the damage occurred and demonstrated the underlying factors for damage along the SC. This will enable the development of practical interventions to improve the quality and minimize wastage of bananas in the retail markets.